Systematic Literature Review: Gaps and Solutions in the Implementation of Enterprise Architecture in the Digitalization of Healthcare Facilities in Indonesia - Widdy Chandra Permana; Muhammad Azhar Rasyad; Imelda Imelda (Dinasti International Journal of Education Management And Social Science, 2025)
The digitalization of healthcare facilities in Indonesia faces various challenges, including infrastructure imbalances, limited system interoperability, and a lack of human resource readiness in implementing Enterprise Architecture (EA). This study aims to analyze the role of TOGAF ADM 10 as an EA approach in supporting the digital transformation of healthcare facilities. The research method used is a Systematic Literature Review (SLR), reviewing 12 previous studies related to the implementation of EA in healthcare services. The findings indicate that TOGAF ADM 10 offers advantages in enhancing health information system interoperability, ensuring data security, and aligning with national policies. Compared to its previous versions, TOGAF ADM 10 provides a more flexible and modular approach, enabling more efficient system integration without disrupting existing infrastructure. Thus, this study contributes to understanding optimal EA implementation strategies to accelerate the digitalization of healthcare services in Indonesia.